(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The Search stressed on the importance of the role of property tax as a tributaries of the state budget that depend on it to cover the side of public expenditures, along with the rest of the other types of taxes through a review of the tax framework and tax proceeds and stand on the research problem and its effects, according to the following logic questions : - • What is the contribution of property tax in the overall tax revenue? • Are there any certain problems in collection of property tax? 3. What are the factors that lead to a negative impact on the outcome of the property tax? 4. How do we strengthen the role of the property tax in the overall tax revenue? This research has been aiming to recognition of property tax role starting from hypothesis as follows:- The main hypothesis:- there is liaison of statistic significance between the proceeds derived from the property tax and the factors by which it is influenced). A correlation relationship of statistical. • There is liaison of statistic significance between tax property and the average of tax proceeding. • There is a correlation relationship of statistical significance between tax property and the factors related to the taxpayer. • There is a correlation relationship of statistical between tax property and the factors related with the tax management. • There is a correlation relationship of statistical between tax property and the factors related with economic and legislative situations. After testing the hypothesis research using appropriate statistical tools, was a number of Conclusions and recommendations have been summarized as follow:- Weakness of tax awareness for the taxpayer has led to decline the tax proceedings. In addition to the negative effect to Deterioration of security situation in assessment of properties in site for the difficulty of reaching them by the supervisor that shown as (84,3%) of the sample which is reflected in tax revenue, and this leads to necessarily the recommendation To find an efficient methods that enable tax authority to perform assessment of properties values via cooperation with the military forces or forming police system affiliated with the body of public taxation, then the necessity of raising the tax awareness level for the taxpayer and to make tax laws available for all and to work towards achieving the optional tax compliance to reduce tax evasion and to increase the tax proceedings. المقدمة